ChemInform Abstract: Asymmetric Dual Catalysis via Fragmentation of a Single Rhodium Precursor Complex. Issue 42 (September 2016) - Song, Liangliang; Gong, Lei; Meggers, Eric
Abstract: A newly synthesized single rhodium complex is used as an efficient catalyst in the Michael reaction of 2‐acyl imidazoles with α, α‐disubstituted aldehydes.